Electromagnetic wave shield sheet
Patent Information
- Application Number
- JP2023148439
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-13
- Publication Date
- 2025-03-26
AI Technical Summary
【0008】 本発明の電磁波シールドシートは、所定の層構成とすることにより、非常に薄いシートとした場合であっても電磁波シールド性に優れている。
Smart Images

Figure 2025041253000001 
Figure 2025041253000002
Abstract
Description
[Technical field]
[0001] The present invention relates to an electromagnetic wave shielding sheet. [Background technology]
[0002] Electromagnetic waves generated from various devices such as printed wiring boards, electronic components, and antennas interfere with each other, and may affect other electric circuits and electronic components, causing malfunctions, etc. Therefore, there is a demand for preventing malfunctions of various devices by using electromagnetic wave shielding sheets to improve the electromagnetic shielding properties of the various devices.
[0003] As an electromagnetic wave shielding sheet, for example, Patent Document 1 discloses a multilayer material for shielding low-frequency electromagnetic waves, the multilayer material including a plurality of repeating material alternating layer sets, each of which includes a conductive layer and a magnetic layer. Patent Document 2 discloses a non-flammable electromagnetic wave shielding laminate including an aluminum foil layer, an adhesive layer, and a base layer, the aluminum foil layer being the outermost layer on one or both sides of the non-flammable electromagnetic wave shielding laminate, the adhesive layer being a layer that bonds the aluminum foil layer, and the base layer including a spunbond layer. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent Publication No. 2022-75645 [Patent Document 2] JP 2019-179786 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, Patent Document 1 states that it is specialized in shielding electromagnetic waves having frequencies less than about 1 MHz, and Figures 2 to 4, which are given as specific examples of multilayer materials, disclose only multilayer materials having multiple sets of alternating conductive and magnetic layers, and there is a problem that such a laminate structure has insufficient electromagnetic shielding properties at frequencies of about 10 to 100 MHz. Also, although Patent Document 2 is an invention related to an electromagnetic shielding laminate, it aims to increase heat resistance by including a spunbond layer, and there is room for improvement in electromagnetic shielding properties.
[0006] An object of the present invention is to provide an electromagnetic wave shielding sheet having excellent electromagnetic wave shielding properties. [Means for solving the problem]
[0007] That is, the present invention includes the following inventions. [1] An electromagnetic shielding sheet comprising a first conductive layer, a second conductive layer and a third conductive layer, one main surface of the electromagnetic shielding sheet being the first conductive layer and the other main surface being the second conductive layer, the third conductive layer being between the first conductive layer and the second conductive layer, a first magnetic layer being between the first conductive layer and the third conductive layer, and a second magnetic layer being between the third conductive layer and the second conductive layer, the first conductive layer, the second conductive layer and the third conductive layer all having a laminated structure in which a conductive film having a thickness of 25 to 150 nm is formed on at least one surface of a resin layer, and the first magnetic layer and the second magnetic layer all contain a magnetic material. [2] The electromagnetic wave shielding sheet according to [1], wherein the conductive material constituting the conductive film includes at least one selected from the group consisting of conductive polymers, metals, metal oxides, and carbon-based materials. [3] The electromagnetic wave shielding sheet according to [1] or [2], wherein the magnetic material is a soft magnetic material. [4] The electromagnetic shielding sheet according to any one of [1] to [3], wherein the total thickness of the conductive films included in the electromagnetic shielding sheet is 3 μm or less. [5] The electromagnetic shielding sheet according to any one of [1] to [4] above, further comprising a nonwoven fabric layer as an intermediate layer. [6] The electromagnetic shielding sheet according to [5], wherein the nonwoven fabric layer contains a polyester resin. [7] An electromagnetic wave shielding sheet according to any one of [1] to [6], having a thickness of 900 μm or less, a magnetic field shielding property at 100 MHz measured by the KEC method of 20 dB or more, and an electric field shielding property at 10 MHz of 70 dB or more. Effect of the Invention
[0008] The electromagnetic wave shielding sheet of the present invention has a predetermined layer structure, and therefore has excellent electromagnetic wave shielding properties even when made into a very thin sheet. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The electromagnetic shielding sheet of the present invention comprises a first conductive layer, a second conductive layer, and a third conductive layer, one of the main surfaces being the first conductive layer and the other main surface being the second conductive layer, where the main surface refers to the surface perpendicular to the lamination direction (thickness direction) of the electromagnetic shielding sheet.
[0010] In addition, the electromagnetic wave shielding sheet of the present invention has a third conductive layer between the first conductive layer and the second conductive layer, includes a first magnetic layer between the first conductive layer and the third conductive layer, and includes a second magnetic layer between the third conductive layer and the second conductive layer.
[0011] <Conductive layer> The first conductive layer, the second conductive layer, and the third conductive layer each have a laminated structure in which a conductive film having a thickness of 25 to 150 nm is formed on at least one surface of a resin layer. In other words, the laminated structure of the first conductive layer, the second conductive layer, and the third conductive layer is a laminated structure of resin layer / conductive film or conductive film / resin layer / conductive film.
[0012] The resin constituting the resin layer is not particularly limited as long as it does not impair the electromagnetic wave shielding properties, but it preferably contains at least one resin selected from the group consisting of polyolefin resin, polyester resin, polyamide resin, polyurethane resin, and acrylic resin, more preferably contains polyester resin, and even more preferably contains polyethylene terephthalate resin.
[0013] The conductive film is a layer formed from a conductive material, and is not particularly limited as long as it has a thickness of 25 to 150 nm. The conductive material contained in the conductive film will be described later.
[0014] The electromagnetic shielding sheet of the present invention may include a conductive layer in addition to the first to third conductive layers. Hereinafter, the conductive layers other than the first to third conductive layers are referred to as "other conductive layers". The other conductive layers may have the above-mentioned laminated structure or may be layers mainly made of a conductive material, but the above-mentioned laminated structure is preferable. In the present invention, by making the layer structure predetermined, a sheet having excellent electromagnetic shielding properties can be obtained without using a layer mainly made of a conductive material. Therefore, in the present invention, the electromagnetic shielding sheet of the present invention preferably does not have a conductive layer having a thickness of more than 3 μm and containing 90% or more of a conductive material, more preferably does not have a conductive layer having a thickness of more than 1 μm and containing 90% or more of a conductive material, and even more preferably does not have a conductive layer having a thickness of more than 150 nm and containing 90% or more of a conductive material.
[0015] Other conductive layers mainly made of conductive material may contain 90% by mass or more of conductive material, and may also contain 100% by mass (conductive layer consisting of only conductive material).
[0016] Preferred embodiments of the conductive layer are described below, and unless otherwise specified, the term "conductive layer" refers to the first conductive layer, the second conductive layer, the third conductive layer, and each of the other conductive layers, and the term "conductive film" refers to each of the conductive films provided on the first conductive layer, the second conductive layer, the third conductive layer, and each of the other conductive layers.
[0017] The conductive material contained in the conductive film or other conductive layer mainly made of a conductive material is not particularly limited, but preferably contains at least one selected from the group consisting of conductive polymers, metals, metal oxides, and carbon-based materials, and more preferably is a metal. The conductive material may be only one type or two or more types.
[0018] Examples of conductive polymers include polyacetylene, polypyrrole, poly(3,4-ethylenedioxythiophene), poly(3,4-ethylenedioxythiophene) / polystyrenesulfonate, polythiophene, polyaniline, poly(p-phenylene), polyfluorene, polycarbazole, and polysilane.
[0019] Examples of metals include elemental metals such as gold, silver, copper, and aluminum; and alloys containing one or more of these elemental metals, with aluminum being preferred.
[0020] Examples of metal oxides include tin-doped indium oxide (ITO), antimony-doped tin oxide (ATO), and fluorine-doped tin oxide (FTO).
[0021] Examples of carbon-based materials include compounds having a carbon skeleton, such as carbon nanotubes, carbon nanofibers, CN nanotubes, CN nanofibers, BCN nanotubes, BCN nanofibers, graphene, carbon microcoils, carbon nanocoils, carbon nanohorns, carbon nanowalls, and carbon black.
[0022] The thickness of the conductive layer is preferably 4 to 100 μm, more preferably 6 to 60 μm, further preferably 8 to 40 μm, and particularly preferably 10 to 20 μm. In the present invention, by giving the electromagnetic shielding sheet a predetermined layer structure, it is possible to improve the electromagnetic shielding properties even in an electromagnetic shielding sheet in which the conductive layer is very thin, 100 μm or less per layer.
[0023] The weight of the conductive layer is 5 to 100 g / m 2 It is preferable that the thickness is 10 to 70 g / m 2 More preferably, the thickness is 15 to 40 g / m 2 In the present invention, by forming the electromagnetic wave shielding sheet into a predetermined layer structure, the conductive layer has a weight of 100 g / m per single layer. 2 Even with a low basis weight of 0.1 or less, the electromagnetic wave shielding properties can be improved.
[0024] In the conductive layer, a conductive film having a thickness of 25 to 150 nm is formed on at least one surface of the resin layer, and a conductive film having a thickness of 30 to 100 nm is preferably formed on at least one surface of the resin layer, more preferably a conductive film having a thickness of 35 to 75 nm is formed on at least one surface of the resin layer, and even more preferably a conductive film having a thickness of 40 to 60 nm is formed on at least one surface of the resin layer. In other words, in the present invention, an electromagnetic wave shielding sheet that does not contain a conductive film having a thickness exceeding the above-mentioned upper limit can be obtained, and even if an electromagnetic wave shielding sheet does not contain a conductive film having a thickness exceeding the above-mentioned upper limit, it can improve the electromagnetic wave shielding property by forming a predetermined layer structure. The method of forming the conductive film is not particularly limited, and examples thereof include methods such as vapor deposition, sputtering, and vapor phase growth. In the case of a conductive layer in which a conductive film is provided on both sides of a resin layer, it is preferable that the thickness of both sides is within the above range.
[0025] The total thickness of all conductive layers is preferably 200 μm or less, more preferably 150 μm or less, even more preferably 100 μm or less, particularly preferably 75 μm or less, and most preferably 50 μm or less. In the present invention, by making the electromagnetic wave shielding sheet have a predetermined layer structure, even a very thin electromagnetic wave shielding sheet having a total thickness of the conductive layers of 200 μm or less has excellent electromagnetic wave shielding properties. The lower limit of the thickness is not particularly limited, but is, for example, 10 μm or more, and preferably 20 μm or more.
[0026] The total weight of all conductive layers is 20 to 200 g / m 2It is preferable that the thickness is 30 to 150 g / m 2 More preferably, the thickness is 40 to 100 g / m 2 In the present invention, by forming the electromagnetic wave shielding sheet into a predetermined layer structure, the total conductive layer weight is preferably 200 g / m 2 Even with a basis weight as low as or less, it has excellent electromagnetic wave shielding properties.
[0027] The total thickness of all the conductive films is preferably 3 μm or less, more preferably 30 nm to 1 μm, even more preferably 50 to 800 nm, particularly preferably 100 to 500 nm, and most preferably 150 to 300 nm. In the present invention, by giving the electromagnetic shielding sheet a predetermined layer structure, even an extremely thin electromagnetic shielding sheet having a total thickness of the conductive films of 3 μm or less has excellent electromagnetic shielding properties.
[0028] The distance between the first conductive layer and the third conductive layer is preferably 50 to 500 μm, more preferably 75 to 400 μm, even more preferably 100 to 300 μm, and particularly preferably 125 to 200 μm. In the present invention, when the electromagnetic shielding sheet has the above-mentioned layer structure, the conductive film provided on the first conductive layer and the conductive film provided on the third conductive layer are positioned at an appropriate distance from each other, thereby improving the electromagnetic shielding properties. The distance between the second conductive layer and the third conductive layer is preferably 50 to 500 μm, more preferably 75 to 400 μm, even more preferably 100 to 300 μm, and particularly preferably 125 to 200 μm. In the present invention, when the electromagnetic shielding sheet has the above-mentioned layer structure, the conductive film provided on the second conductive layer and the conductive film provided on the third conductive layer are positioned at an appropriate distance from each other, thereby improving the electromagnetic shielding properties. The distance between the first conductive layer and the third conductive layer refers to the distance between the surface of the first conductive layer closest to the third conductive layer and the surface of the third conductive layer closest to the first conductive layer, and the distance between the second conductive layer and the third conductive layer refers to the distance between the surface of the second conductive layer closest to the third conductive layer and the surface of the third conductive layer closest to the second conductive layer.
[0029] When at least one of the first conductive layer and the second conductive layer has a laminated structure in which a conductive film is formed only on one surface of the resin layer (a laminated structure of resin layer / conductive film), the electromagnetic wave shielding property is not significantly affected whether the resin layer or the conductive film is located on the main surface side. Therefore, when the first conductive layer and the second conductive layer both have a laminated structure in which a conductive film is formed only on one surface of the resin layer, one main surface may be a resin layer and the other main surface may be a conductive film, both main surfaces may be conductive films, or both main surfaces may be resin layers. Note that when both the first conductive layer and the second conductive layer have a laminated structure in which a conductive film is formed on both surfaces of the resin layer (a laminated structure of conductive film / resin layer / conductive film), both main surfaces of the electromagnetic wave shielding sheet of the present invention are conductive films.
[0030] <Magnetic layer> Both the first magnetic layer and the second magnetic layer contain a magnetic material. The magnetic material preferably contains at least one selected from the group consisting of metals and metal oxides, and more preferably is a metal. Examples of the metal include simple metals such as iron, nickel, and cobalt; sendust (Fe-Si-Al alloy), silicon steel (Fe-Si alloy), Fe-Al alloy, permalloy (Fe-Ni alloy), magnetic stainless steel (Fe-Cr-Al-Si alloy), silicon copper (Fe-Cu-Si alloy), Fe-Si-Cr alloy, Fe-Si-Al-Ni alloy, Fe-Ni-Si-Co alloy, Fe-Ni-Si-Co-Cr alloy, Fe-based amorphous alloy, Fe-based nanocrystalline alloy, and other alloys; and examples of the metal oxide include ferrite represented by AFe2O4 (A is Mn, Co, Ni, Cu, or Zn). Among these, soft magnetic materials such as iron, sendust, Fe-Si alloy, permalloy, magnetic stainless steel, and silicon copper are preferable, and sendust is more preferable.
[0031] The electromagnetic wave shielding sheet of the present invention may include a magnetic layer in addition to the first magnetic layer and the second magnetic layer. Hereinafter, the magnetic layers other than the first magnetic layer and the second magnetic layer are referred to as "other magnetic layers." The other magnetic layers also include a magnetic material, and the magnetic material included in the other magnetic layers is as described above.
[0032] Preferred embodiments of the magnetic layer will be described below, and unless otherwise specified, the term "magnetic layer" refers to the first magnetic layer, the second magnetic layer, and any other magnetic layers.
[0033] The magnetic layer preferably contains a resin in addition to the magnetic material. When the magnetic layer contains a resin, the content of the resin in the magnetic layer relative to 100 parts by mass of the magnetic material is preferably 30 to 200 parts by mass, more preferably 40 to 160 parts by mass, and even more preferably 50 to 120 parts by mass.
[0034] The resin constituting the magnetic layer is preferably a thermoplastic resin, specifically at least one selected from the group consisting of polyester-based resins, polyester urethane-based resins, polyamide-based resins, polyamideimide-based resins, phenoxy-based resins, olefin-based resins, and acrylic-based resins, with polyester-based resins being more preferred.
[0035] The resin constituting the magnetic layer may be a crosslinked thermoplastic resin in which a thermoplastic resin is crosslinked by a crosslinking agent, and is preferably a crosslinked polyester resin in which a polyester resin is crosslinked by a crosslinking agent. The crosslinking agent is not particularly limited and can be appropriately selected depending on the purpose, but examples thereof include isocyanate-based crosslinking agents, melamine-based crosslinking agents, and epoxy-based crosslinking agents, and is preferably an isocyanate-based crosslinking agent. In addition, as the crosslinking agent, commercially available products may be used. For example, as an isocyanate-based crosslinking agent, Millionate (registered trademark) N, Coronate (registered trademark) T, Coronate (registered trademark) HL, Coronate (registered trademark) 2030, Suprasec (registered trademark) 3340, Daltosec 1350, Daltosec 2170, Daltosec 2280 (all manufactured by Nippon Polyurethane Industry Co., Ltd.) and the like can be mentioned. As a melamine-based crosslinking agent, Nikalac (registered trademark) MS-11, Nikalac (registered trademark) MS21 (all manufactured by Sanwa Chemical Co., Ltd.), Super Beckamine (registered trademark) L-105-60, Super Beckamine (registered trademark) J-820-60 (all manufactured by DIC Corporation) and the like can be mentioned. As an epoxy-based crosslinking agent, Hardener HY951, Hardener HY957 (all manufactured by BASF), Sumicure DTA, Sumicure TTA (all manufactured by Sumitomo Chemical Co., Ltd.) and the like can be mentioned. Among these, polyfunctional isocyanate compounds are more preferable, and a commercially available product thereof is Coronate (registered trademark) HL manufactured by Tosoh Corporation, which is a trimer adduct of trimethylolpropane and hexamethylene diisocyanate.
[0036] The thickness of the magnetic layer is preferably 30 to 500 μm, more preferably 50 to 400 μm, further preferably 70 to 350 μm, and particularly preferably 100 to 300 μm. In the present invention, by making the electromagnetic shielding sheet have a predetermined layer structure, even an electromagnetic shielding sheet with a very thin magnetic layer of 500 μm or less per layer has excellent electromagnetic shielding properties.
[0037] The weight of the magnetic layer is 50 to 400 g / m 2 It is preferable that the thickness is 70 to 300 g / m 2More preferably, the thickness is 100 to 250 g / m 2 More preferably, the thickness is 120 to 200 g / m 2 In the present invention, by forming the electromagnetic wave shielding sheet into a predetermined layer structure, the magnetic layer has a weight of 400 g / m per single layer. 2 Even with a basis weight as low as or less, it has excellent electromagnetic wave shielding properties.
[0038] The weight of the magnetic material alone in the magnetic layer is 30 to 350 g / m 2 It is preferable that the thickness is 50 to 300 g / m 2 More preferably, the thickness is 70 to 200 g / m 2 More preferably, the thickness is 90 to 150 g / m 2 In the present invention, the electromagnetic wave shielding sheet has a predetermined layer structure, and the weight per single layer is preferably 350 g / m 2 Even with a small amount of magnetic material of less than 1000g / m2, excellent electromagnetic wave shielding properties are achieved.
[0039] The total thickness of all the magnetic layers is preferably 50 to 700 μm, more preferably 100 to 600 μm, even more preferably 150 to 500 μm, and particularly preferably 200 to 400 μm. In the present invention, by giving the electromagnetic shielding sheet a predetermined layer structure, even a very thin electromagnetic shielding sheet having a total thickness of the magnetic layers of 700 μm or less has excellent electromagnetic shielding properties.
[0040] The total weight of all magnetic layers is 10 to 700 g / m 2 It is preferable that the thickness is 150 to 500 g / m 2 More preferably, it is 200 to 400 g / m 2 In the present invention, by forming the electromagnetic wave shielding sheet into a predetermined layer structure, the total magnetic layer weight is 700 g / m 2 Even with a basis weight as low as or less, it has excellent electromagnetic wave shielding properties.
[0041] In the electromagnetic wave shielding sheet of the present invention, the total basis weight of the magnetic material alone is 50 to 500 g / m 2 It is preferable that the thickness is 70 to 400 g / m 2 More preferably, the thickness is 100 to 300 g / m 2 In the present invention, by forming the electromagnetic wave shielding sheet into a predetermined layer structure, the total weight of the sheet is preferably 500 g / m 2 Even with a small amount of magnetic material of less than 1000g / m2, excellent electromagnetic wave shielding properties are achieved.
[0042] <Nonwoven fabric layer> The electromagnetic shielding sheet of the present invention may further include a nonwoven fabric layer as an intermediate layer. That is, not only a magnetic layer but also a nonwoven fabric layer may be included between the first conductive layer and the third conductive layer or between the third conductive layer and the second conductive layer. By including a nonwoven fabric layer, cushioning properties and elasticity in the thickness direction are improved, and installation in uneven or curved areas becomes easier. The electromagnetic shielding sheet of the present invention may include only one nonwoven fabric layer or two or more nonwoven fabric layers.
[0043] The nonwoven fabric constituting the nonwoven fabric layer is not particularly limited, and examples thereof include polyester nonwoven fabric, polypropylene nonwoven fabric, polyamide nonwoven fabric, and polyurethane nonwoven fabric. However, it is preferable that the nonwoven fabric layer contains a polyester resin, and it is more preferable that the nonwoven fabric constituting the nonwoven fabric layer is a polyester nonwoven fabric.
[0044] The nonwoven fabric constituting the nonwoven fabric layer may be one obtained by a known method such as a dry method, a wet method, a spunbond method, a melt-blowing method, a flash spinning method, a thermal bond method, a chemical bond method, a needle punch method, a spunlace method, a steam jet method, etc. In addition, a commercially available product may be used as the nonwoven fabric constituting the nonwoven fabric layer.
[0045] The thickness of the nonwoven fabric layer is preferably 700 μm or less, more preferably 600 μm or less, and even more preferably 500 μm or less. The lower limit of the thickness is not particularly limited, but is, for example, 100 μm or more, and preferably 200 μm or more. In addition, when the electromagnetic wave shielding sheet is provided with multiple nonwoven fabric layers, the thickness of the nonwoven fabric layer mentioned above refers to the total thickness of all the nonwoven fabric layers provided on the electromagnetic wave shielding sheet.
[0046] The weight of the nonwoven layer is 20 to 300 g / m 2 It is preferable that the thickness is 40 to 200 g / m 2 More preferably, the thickness is 60 to 150 g / m 2 It is more preferable that the weight per unit area of the nonwoven fabric layer is the total weight per unit area of the nonwoven fabric layer. When the electromagnetic wave shielding sheet has a plurality of nonwoven fabric layers, the weight per unit area of the nonwoven fabric layer refers to the total weight per unit area of the nonwoven fabric layers.
[0047] <Binder layer> In laminating a conductive layer and a magnetic layer, a conductive layer and a nonwoven fabric layer, and a magnetic layer and a nonwoven fabric layer, a binder layer may be interposed between the layers, if necessary.
[0048] The binder layer is formed from a resin composition. The resin constituting the binder layer is preferably a thermoplastic resin, specifically, at least one selected from the group consisting of polyester-based resins, polyester urethane-based resins, polyamide-based resins, polyamideimide-based resins, phenoxy-based resins, olefin-based resins, and acrylic-based resins, and more preferably a polyester-based resin.
[0049] The resin composition for forming the binder layer may contain a crosslinking agent in addition to the resin. The binder layer may contain a crosslinked thermoplastic resin obtained by crosslinking a thermoplastic resin, and preferably contains a crosslinked polyester resin obtained by crosslinking a polyester resin. The crosslinking agent is not particularly limited and can be appropriately selected according to the purpose, and examples thereof include isocyanate-based crosslinking agents, melamine-based crosslinking agents, and epoxy-based crosslinking agents, and is preferably an isocyanate-based crosslinking agent. In addition, as the crosslinking agent, commercially available products may be used. For example, as an isocyanate-based crosslinking agent, Millionate (registered trademark) N, Coronate (registered trademark) T, Coronate (registered trademark) HL, Coronate (registered trademark) 2030, Suprasec (registered trademark) 3340, Daltosec 1350, Daltosec 2170, Daltosec 2280 (all manufactured by Nippon Polyurethane Industry Co., Ltd.) and the like can be mentioned. As a melamine-based crosslinking agent, Nikalac (registered trademark) MS-11, Nikalac (registered trademark) MS21 (all manufactured by Sanwa Chemical Co., Ltd.), Super Beckamine (registered trademark) L-105-60, Super Beckamine (registered trademark) J-820-60 (all manufactured by DIC Corporation) and the like can be mentioned. As an epoxy-based crosslinking agent, Hardener HY951, Hardener HY957 (all manufactured by BASF), Sumicure DTA, Sumicure TTA (all manufactured by Sumitomo Chemical Co., Ltd.) and the like can be mentioned. Among these, polyfunctional isocyanate compounds are more preferable, and a commercially available product thereof is Coronate HL manufactured by Tosoh Corporation, which is a trimer adduct of trimethylolpropane and hexamethylene diisocyanate.
[0050] <Physical properties and layer structure of electromagnetic wave shielding sheet> The electromagnetic shielding sheet of the present invention preferably has a thickness of 900 μm or less, more preferably 800 μm or less, even more preferably 600 μm or less, particularly preferably 500 μm or less, and most preferably 400 μm or less. In the present invention, the electromagnetic shielding sheet has a predetermined layer structure, so that even a very thin electromagnetic shielding sheet having a thickness of 900 μm or less has excellent electromagnetic shielding properties. The lower limit of the thickness is not particularly limited, but is, for example, 50 μm or more, and preferably 100 μm or more.
[0051] The electromagnetic wave shielding sheet of the present invention has a basis weight of 2000 g / m 2 It is preferable that the thickness is less than 1500 g / m 2 More preferably, it is 1000 g / m or less. 2 More preferably, it is 700 g / m or less. 2 It is particularly preferable that the weight is 500 g / m or less. 2 It is most preferable that the weight per unit area is 2000 g / m or less. 2 Even with a basis weight as low as 100 g / m or less, the sheet has excellent electromagnetic shielding properties. 2 More than 200g / m 2 More preferably, it is equal to or greater than this.
[0052] The electromagnetic wave shielding sheet of the present invention preferably has a magnetic field shielding property of 20 dB or more, more preferably 25 dB or more, at 100 MHz as measured by the KEC method. The upper limit of the magnetic field shielding property is not particularly limited, but is, for example, 99 dB or less.
[0053] The electromagnetic wave shielding sheet of the present invention preferably has an electric field shielding property of 70 dB or more, more preferably 75 dB or more, at 10 MHz as measured by the KEC method. The upper limit of the electric field shielding property is not particularly limited, but is, for example, 99 dB or less.
[0054] Detailed methods for measuring the magnetic shielding property at 100 MHz measured by the KEC method and the electric field shielding property at 10 MHz by the KEC method will be described later. In the present invention, in an extremely thin electromagnetic shielding sheet having a thickness of 900 μm or less, it is preferable that the magnetic field shielding property at 100 MHz measured by the KEC method is 20 dB or more, and the electric field shielding property at 10 MHz is 70 dB or more. In the present invention, by making the electromagnetic shielding sheet have a predetermined layer structure, it has excellent electromagnetic shielding property even if it is extremely thin, having a thickness of 900 μm or less.
[0055] The electromagnetic wave shielding sheet of the present invention is not particularly limited as long as it has a layer structure in which one main surface is a first conductive layer, the other main surface is a second conductive layer, the third conductive layer is between the first conductive layer and the second conductive layer, a first magnetic layer is between the first conductive layer and the third conductive layer, and a second magnetic layer is between the third conductive layer and the second conductive layer. For example, the layer structure may be conductive layer / magnetic layer / conductive layer / magnetic layer / conductive layer, conductive layer / magnetic layer / conductive layer / magnetic layer / conductive layer, conductive layer / magnetic layer / conductive layer / magnetic layer / nonwoven fabric layer / conductive layer, conductive layer / magnetic layer / nonwoven fabric layer / conductive layer / magnetic layer / conductive layer, conductive layer / magnetic layer / nonwoven fabric layer / conductive layer / magnetic layer / conductive layer, conductive layer / magnetic layer / nonwoven fabric layer / conductive layer / magnetic layer / nonwoven fabric layer / conductive layer, conductive layer / magnetic layer / binder layer / conductive layer / magnetic layer / binder layer / conductive layer, conductive layer / magnetic layer / binder layer / conductive layer, conductive layer / magnetic layer / binder layer / conductive layer. Examples of layer configurations include: conductive layer / magnetic layer / binder layer / conductive layer / magnetic layer / binder layer / conductive layer; conductive layer / magnetic layer / binder layer / conductive layer / magnetic layer / binder layer / nonwoven fabric layer / binder layer / conductive layer; conductive layer / magnetic layer / binder layer / nonwoven fabric layer / binder layer / conductive layer / magnetic layer / conductive layer; conductive layer / magnetic layer / binder layer / nonwoven fabric layer / binder layer / conductive layer / magnetic layer / conductive layer; conductive layer / magnetic layer / binder layer / nonwoven fabric layer / binder layer / conductive layer / magnetic layer / binder layer / nonwoven fabric layer / binder layer / conductive layer / magnetic layer / binder layer / nonwoven fabric layer / binder layer / conductive layer.
[0056] <Manufacturing method of electromagnetic wave shielding sheet> The manufacturing method of the electromagnetic wave shielding sheet is not particularly limited and the sheet can be manufactured by known methods. However, the following describes a manufacturing method in which the conductive layer and the nonwoven fabric layer are commercially available products (finished products), while the magnetic layer is not a commercially available product but is formed using a resin composition for the magnetic layer.
[0057] When a magnetic layer is formed on the surface of a conductive layer, a resin composition for a magnetic layer is applied to the surface of the conductive layer by a method such as coating, vapor deposition, or sputtering, and then dried to obtain a laminate in which the conductive layer / magnetic layer are laminated in this order. In this specification, the "surface" refers to a surface perpendicular to the lamination direction (thickness direction) of the electromagnetic shielding sheet.
[0058] When a nonwoven fabric layer is formed on the surface of a conductive layer, or when another layer is formed on the surface of a magnetic layer or a nonwoven fabric layer, the layers can be laminated via a binder layer. For example, when a nonwoven fabric layer is formed on the surface of a conductive layer, a resin composition for binder layer is applied to the surface of the conductive layer by a method such as coating, and then a nonwoven fabric is attached to the surface of the resin composition for binder layer, followed by drying and thermocompression bonding to obtain a laminate in which the conductive layer / binder layer / nonwoven fabric layer are laminated in this order. The drying and thermocompression bonding may be performed by a known method, for example, at a temperature of 100 to 150° C. and a pressure of 1 to 20 N / cm. 2 This can be done by hot pressing at a pressure of 1000 .mu.m. EXAMPLES
[0059] The present invention will be described below with reference to examples, but the present invention is not limited to these examples. The evaluation methods used in each example and comparative example are as follows.
[0060] (Measurement of unit weight) The basis weight was measured based on "Mass per unit area" in JIS L 1913 (2010) 6.2.
[0061] (Thickness measurement) The thickness of the sample (laminate sheet) was measured based on 6.1 of JIS L 1913 (2010). The thicknesses of the vapor-deposited film and aluminum foil were measured based on JIS H 4160. The thickness of the vapor-deposited film was measured using a transmission electron microscope, and the thicknesses of the magnetic layer and binder layer were measured by cutting the laminate sheet vertically and taking enlarged photographs of the cut surfaces using an electron microscope.
[0062] (Measurement of magnetic field shielding at a frequency of 100 MHz) A sample (laminate sheet) measuring 150 mm in length and 150 mm in width was prepared, and an electromagnetic shielding effectiveness measuring device developed by the Kansai Electronics Industry Development Center (KEC) was used to measure the magnetic field strength M (A / m) in a space where the sample was not present, and the magnetic field strength M' (A / m) when the sample was placed, at a frequency of 100 MHz. The magnetic field shielding performance at a frequency of 100 MHz was then calculated using the following formula. Magnetic field shielding performance (dB) = 20 log 10 (M / M')
[0063] (Measurement of electric field shielding at a frequency of 10 MHz) A sample (laminate sheet) measuring 150 mm in length and 150 mm in width was prepared, and an electromagnetic shielding effectiveness measuring device developed by the Kansai Electronics Industry Development Center (KEC) was used to measure the electric field strength E (V / m) in a space where the sample was not present, and the electric field strength E' (V / m) when the sample was placed, at a frequency of 10 MHz. The electric field shielding performance at a frequency of 10 MHz was then calculated using the following formula. Electric field shielding performance (dB) = 20 log 10 (E / E')
[0064] <Method of manufacturing resin composition for magnetic layer> 100 parts of resin (Byron BX-1001 manufactured by Toyobo Co., Ltd.), magnetic material (Sendust manufactured by Kinseimatic Co., Ltd.), and 250 parts of solvent (150 parts of methyl ethyl ketone, 100 parts of N,N-dimethylformamide) were mixed and heated to 30° C. The amount of magnetic material blended was determined according to the ratio of magnetic material to resin in the magnetic layer. For example, when the basis weight of the magnetic layer was 150 g / m 2 The weight of the resin in the magnetic layer is 50 g / m 2 , the weight of the magnetic material is 100g / m 2When it was desired to achieve the above, 228 parts of the magnetic material was added, which is twice the total amount of the resin and the crosslinking agent described below. Next, the resin was dissolved using a stirrer, and then 14 parts of a crosslinking agent (Tosoh's Coronate HL) was added to the solution to obtain a resin composition for magnetic layers. In Examples 1-3, 1-4, 2-3, and 2-4, ferrite was used instead of sendust as the magnetic material, and the ferrite contained 13 mass% magnetite, 58 mass% manganese ferrite, and 29 mass% zinc ferrite.
[0065] <Method for producing resin composition for binder layer> 100 parts of resin (Vylon BX-1001 manufactured by Toyobo Co., Ltd.) and 200 parts of solvent (methyl ethyl ketone) were mixed and heated to 30°C. Next, the resin was dissolved using a stirrer, and then 14 parts of a crosslinking agent (Coronate HL manufactured by Tosoh Corporation) was added to the solution to obtain a resin composition for binder layers. Note that the binder layers formed in the following examples and comparative examples all had a thickness of 10 μm and a basis weight of 30 g / m. 2 It is.
[0066] <Double-sided vapor deposition film, single-sided vapor deposition film, aluminum foil, and polyester nonwoven fabric> As the double-sided deposition film used in the following examples and comparative examples, a film manufactured by Saichi Kogyo Co., Ltd. was prepared in which aluminum was deposited on both sides of a biaxially stretched polyethylene terephthalate film. The total thickness of the double-sided deposition film was 12 μm, the thickness of the deposition layer was 42 nm on each side, and the total thickness of the deposition layer was 84 nm. As the single-sided deposition film used in the following examples and comparative examples, a film manufactured by Saichi Kogyo Co., Ltd. was prepared in which aluminum was deposited on one side of a biaxially stretched polyethylene terephthalate film. The total thickness of the single-sided deposition film was 12 μm, and the thickness of the deposition layer was 45 nm. The thickness of the deposition layer was measured using a transmission electron microscope. The aluminum foil used in the following comparative examples has a thickness of 20 μm and a basis weight of 28 g / m 2 An aluminum foil manufactured by Toyo Aluminium Co., Ltd. was prepared. The polyester nonwoven fabric used in the following Examples and Comparative Examples had a thickness of 215 μm and a basis weight of 42 g / m. 2A polyester spunbond nonwoven fabric (model number: 6401N) manufactured by Toyobo Co., Ltd. was prepared.
[0067] [Example 1-1] A method for manufacturing a laminate sheet in which a double-sided vapor-deposited film (conductive layer) A1, a magnetic layer C1, a binder layer B1, a double-sided vapor-deposited film (conductive layer) A2, a magnetic layer C2, a binder layer B2, and a double-sided vapor-deposited film (conductive layer) A3 are laminated in this order is described below. The magnetic layer resin composition was applied to the double-sided deposition film A2 with a comma coater at 150 g (dry weight) per square meter, and then dried at 150° C. for 3 minutes using a dryer to obtain a laminate L1 including the double-sided deposition film A2 and the magnetic layer C2. Next, the binder layer resin composition was applied to one side of the double-sided deposition film A3 with a comma coater at 30 g (dry weight) per square meter, and the magnetic layer C2 side of the laminate L1 was bonded to the surface of the applied binder layer resin composition. After that, it was dried in a dryer at 120° C. for 1 minute, and then dried at 60° C. and 10 N / cm. 2 and then allowed to stand at room temperature for 48 hours to obtain a laminate L2 in which the double-sided vapor-deposited film A2, the magnetic layer C2, the binder layer B2, and the double-sided vapor-deposited film A3 were laminated in this order. Next, the above-mentioned resin composition for the magnetic layer was applied to the double-sided deposition film A1 by a comma coater so as to be 150 g (dry weight) per square meter, and then dried for 3 minutes at 150°C using a dryer to form a magnetic layer C1 on the surface of the double-sided deposition film A1. Next, the above-mentioned resin composition for the binder layer was applied to the surface of the magnetic layer C1 by a comma coater so as to be 30 g (dry weight) per square meter, and the surface of the laminate L2 on the side of the double-sided deposition film A2 was attached to the surface of the applied resin composition for the binder layer, and then dried for 1 minute in a dryer at 120°C, and then dried at 60°C and 10 N / cm 2 The magnetic layer C1 was thermocompressed under a pressure of 150 g / m2 and then left at room temperature for 48 hours to obtain a laminated sheet. 2 The basis weight of the sendust, which is the magnetic material in the magnetic layer C1, is 100 g / m 2 The same was true for the magnetic layer C2.
[0068] [Example 1-2] A method for producing a laminated sheet in which a single-sided vapor-deposited film (conductive layer) A1, a magnetic layer C1, a binder layer B1, a single-sided vapor-deposited film (conductive layer) A2, a magnetic layer C2, a binder layer B2, and a single-sided vapor-deposited film (conductive layer) A3 are laminated in this order is described below. If A1 is the upper side and A3 is the lower side, each single-sided vapor-deposited film is laminated in the order of a vapor-deposited layer and a resin layer from the top. The resin composition for the magnetic layer was applied to the resin layer side of the single-sided deposition film A2 with a comma coater at 150 g (dry weight) per square meter, and then dried at 150° C. for 3 minutes using a dryer to obtain a laminate L1 including the single-sided deposition film A2 and the magnetic layer C2. Next, the resin composition for the binder layer was applied to the deposition layer side of the single-sided deposition film A3 with a comma coater at 30 g (dry weight) per square meter, and the magnetic layer C2 side of the laminate L1 was bonded to the surface of the applied resin composition for the binder layer. After drying for 1 minute in a dryer at 120° C., the laminate was dried at 60° C. and 10 N / cm. 2 and then allowed to stand at room temperature for 48 hours to obtain a laminate L2 in which the single-sided vapor-deposited film A2, the magnetic layer C2, the binder layer B2, and the single-sided vapor-deposited film A3 were laminated in this order. Next, the resin composition for the magnetic layer was applied to the resin layer side of the one-sided deposition film A1 with a comma coater at 150 g (dry weight) per square meter, and then dried for 3 minutes at 150° C. using a dryer to form a magnetic layer C1 on the resin layer side of the one-sided deposition film A1. Next, the resin composition for the binder layer was applied to the surface of the magnetic layer C1 with a comma coater at 30 g (dry weight) per square meter, and the deposition layer side surface of the one-sided deposition film A2 of the laminate L2 was bonded to the surface of the applied resin composition for the binder layer, and then dried for 1 minute in a dryer at 120° C., and then dried at 60° C. and 10 N / cm 2 The magnetic layer C1 was thermocompressed under a pressure of 150 g / m2 and then left at room temperature for 48 hours to obtain a laminated sheet. 2 The basis weight of the sendust, which is the magnetic material in the magnetic layer C1, is 100 g / m 2The same was true for the magnetic layer C2.
[0069] [Examples 1-3] Except for changing the composition and application amount of the resin composition for the magnetic layer and changing the magnetic material, thickness, and basis weight of the magnetic layers C1 and C2 to those shown in Table 1, a laminate sheet was prepared in the same manner as in Example 1-1, in which double-sided vapor deposition film A1, magnetic layer C1, binder layer B1, double-sided vapor deposition film A2, magnetic layer C2, binder layer B2, and double-sided vapor deposition film A3 were laminated in that order.
[0070] [Examples 1-4] Except for changing the composition and application amount of the resin composition for the magnetic layer, and changing the magnetic material, thickness, and basis weight of the magnetic layers C1 and C2 to those shown in Table 1, a laminate sheet was prepared in the same manner as in Example 1-2, in which one-sided vapor deposition film A1, magnetic layer C1, binder layer B1, single-sided vapor deposition film A2, magnetic layer C2, binder layer B2, and single-sided vapor deposition film A3 were laminated in that order.
[0071] [Comparative Example 1-1] A laminate sheet was produced in the same manner as in Example 1-1, except that the binder layer B2 and the double-sided vapor deposition film A3 were not provided.
[0072] [Comparative Example 1-2] The above-mentioned resin composition for the magnetic layer was applied to the surface of the double-sided vapor deposition film A1 of the laminate sheet of Comparative Example 1-1 using a comma coater at 150 g (dry weight) per square meter, and then dried at 150°C for 3 minutes using a dryer to obtain a laminate sheet in which a magnetic layer C0 was formed on the surface of the double-sided vapor deposition film A1.
[0073] [Comparative Example 1-3] A laminate sheet was produced in the same manner as in Comparative Example 1-1, except that the thickness of the magnetic layers C1 and C2 was changed to 185 μm.
[0074] [Comparative Example 1-4] Thickness 12μm, basis weight 20g / m 2The above resin composition for magnetic layer was applied to a polyester film manufactured by Toyobo Co., Ltd. using a comma coater, and then dried at 150° C. for 3 minutes using a dryer to form a magnetic layer C1 on the surface of the film, thereby obtaining a laminate sheet.
[0075] [Comparative Example 1-5] A laminate sheet was produced in the same manner as in Comparative Example 1-3, except that aluminum foil was used instead of the double-sided vapor deposition film.
[0076] [Comparative Example 1-6] A laminate sheet was produced in the same manner as in Comparative Example 1-2, except that aluminum foil was used instead of the double-sided vapor deposition film.
[0077] The layer configurations and physical properties of each layer of the laminate sheets in the examples and comparative examples, as well as the shielding properties of the laminate sheets, are shown in Table 1. In the column for the basis weight of the magnetic layer, the values in parentheses are the basis weight of the magnetic material only, not including the resin.
[0078] [Table 1]
[0079] [Example 2-1] A method for producing a laminate sheet in which a double-sided vapor-deposited film (conductive layer) A1, a magnetic layer C1, a binder layer B1, a nonwoven fabric layer N1, a binder layer B2, a double-sided vapor-deposited film (conductive layer) A2, a magnetic layer C3, a binder layer B3, a nonwoven fabric layer N2, a binder layer B4, and a double-sided vapor-deposited film (conductive layer) A3 are laminated in this order is described below. The above resin composition for binder layer was applied to the surface of the double-sided deposition film A3 with a comma coater so as to be 30 g (dry weight) per square meter, and a polyester nonwoven fabric was laminated on the resin composition for binder layer. Thereafter, the polyester nonwoven fabric was dried in a dryer at 120°C for 1 minute, and then dried at 60°C and 10 N / cm 2 The laminate was then allowed to stand at room temperature for 48 hours to obtain a laminate L1 in which the nonwoven fabric layer N2, the binder layer B4, and the double-sided vapor deposition film A3 were laminated in this order. The above-mentioned resin composition for magnetic layer was applied to the surface of the double-sided deposition film A2 by a comma coater so as to be 150 g (dry weight) per square meter, and then dried at 150° C. for 3 minutes by a dryer to form a magnetic layer C3 on the surface of the double-sided deposition film A2, thereby obtaining a laminate L2. The magnetic layer C3 had a basis weight of 150 g / m 2 The weight of the magnetic material, Sendust, is 100 g / m 2 It was. The above-mentioned resin composition for binder layer was applied to the surface of the magnetic layer C3 side of the laminate L2 using a comma coater so as to be 30 g (dry weight) per square meter, and the surface of the nonwoven fabric layer N2 side of the laminate L1 was laminated onto the applied resin composition for binder layer. Thereafter, the laminate was dried in a dryer at 120°C for 1 minute, and then dried at 60°C and 10 N / cm 2 and then allowed to stand at room temperature for 48 hours to obtain a laminate L3 having a double-sided vapor-deposited film A2, a magnetic layer C3, a binder layer B3, a nonwoven fabric layer N2, a binder layer B4, and a double-sided vapor-deposited film A3 laminated in this order. The above-mentioned resin composition for magnetic layer was applied to the surface of double-sided deposition film A1 by a comma coater so as to be 150 g (dry weight) per square meter, and then dried for 3 minutes at 150°C using a dryer to form magnetic layer C1 on the surface of double-sided deposition film A1. Next, the above-mentioned resin composition for binder layer was applied to the surface of magnetic layer C1 by a comma coater so as to be 30 g (dry weight) per square meter, and polyester nonwoven fabric was attached to the surface of the applied resin composition for binder layer, and then dried for 1 minute in a dryer at 120°C, and then dried at 60°C and 10 N / cm 2 The laminate was then heated and pressed under a pressure of 100 g / m2 and left at room temperature for 48 hours to obtain a laminate L4 in which the double-sided deposition film A1, the magnetic layer C1, the binder layer B1, and the nonwoven fabric layer N1 were laminated in this order. The magnetic layer C1 had a basis weight of 150 g / m2. 2 The weight of the magnetic material, Sendust, is 100 g / m 2 It was. The above-mentioned resin composition for binder layer was applied to the surface of the double-sided deposition film A2 side of the laminate L3 by a comma coater so as to be 30 g (dry weight) per square meter, and then the surface of the nonwoven fabric layer N1 side of the laminate L4 was laminated on the resin composition for binder layer applied to the laminate L3. Finally, it was dried in a dryer at 120°C for 1 minute, and then dried at 60°C and 10 N / cm 2 The laminate was then left at room temperature for 48 hours to obtain a laminate sheet.
[0080] [Example 2-2] A method for producing a laminated sheet in which a single-sided vapor-deposited film (conductive layer) A1, a magnetic layer C1, a binder layer B1, a nonwoven fabric layer N1, a binder layer B2, a single-sided vapor-deposited film (conductive layer) A2, a magnetic layer C3, a binder layer B3, a nonwoven fabric layer N2, a binder layer B4, and a single-sided vapor-deposited film (conductive layer) A3 are laminated in this order, as follows: If the A1 side is the upper side and the A3 side is the lower side, each single-sided vapor-deposited film is laminated in the order of a vapor-deposited layer and a resin layer from the top. The resin composition for binder layer was applied to the vapor deposition layer side of the one-sided vapor deposition film A3 with a comma coater so as to be 30 g (dry weight) per square meter, and a polyester nonwoven fabric was laminated on the resin composition for binder layer. Thereafter, the fabric was dried in a dryer at 120°C for 1 minute, and then dried at 60°C and 10 N / cm 2 The laminate was then heated and pressed under a pressure of 100° C. and then allowed to stand at room temperature for 48 hours to obtain a laminate L1 in which the nonwoven fabric layer N2, the binder layer B4, and the one-sided vapor deposition film A3 were laminated in this order. The resin composition for the magnetic layer was applied to the resin layer side of the one-sided deposition film A2 with a comma coater so as to be 150 g (dry weight) per square meter, and then dried at 150°C for 3 minutes with a dryer to form a magnetic layer C3 on the resin layer side of the one-sided deposition film A2, thereby obtaining a laminate L2. The magnetic layer C3 had a basis weight of 150 g / m 2 The weight of the magnetic material, Sendust, is 100 g / m 2 It was. The above-mentioned resin composition for binder layer was applied to the surface of the magnetic layer C3 side of the laminate L2 using a comma coater so as to be 30 g (dry weight) per square meter, and the surface of the nonwoven fabric layer N2 side of the laminate L1 was laminated onto the applied resin composition for binder layer. Thereafter, the laminate was dried in a dryer at 120°C for 1 minute, and then dried at 60°C and 10 N / cm 2 and then allowed to stand at room temperature for 48 hours to obtain a laminate L3 having one-sided vapor-deposited film A2, magnetic layer C3, binder layer B3, nonwoven fabric layer N2, binder layer B4, and one-sided vapor-deposited film A3 laminated in this order. The resin composition for the magnetic layer was applied to the resin layer side of the one-sided deposition film A1 with a comma coater at 150 g (dry weight) per square meter, and then dried for 3 minutes at 150° C. using a dryer to form a magnetic layer C1 on the resin layer side of the one-sided deposition film A1. Next, the resin composition for the binder layer was applied to the surface of the magnetic layer C1 with a comma coater at 30 g (dry weight) per square meter, and a polyester nonwoven fabric was attached to the surface of the applied resin composition for the binder layer, and then dried for 1 minute in a dryer at 120° C. and then dried at 60° C. and 10 N / cm. 2 The laminate was then left at room temperature for 48 hours to obtain a laminate L4 in which the one-sided deposition film A1, the magnetic layer C1, the binder layer B1, and the nonwoven fabric layer N1 were laminated in this order. The magnetic layer C1 had a basis weight of 150 g / m 2 The weight of the magnetic material, Sendust, is 100 g / m 2 It was. The resin composition for the binder layer was applied to the surface of the one-sided deposition film A2 of the laminate L3 at 30 g (dry weight) per square meter using a comma coater, and then the surface of the nonwoven fabric layer N1 of the laminate L4 was laminated on the resin composition for the binder layer applied to the laminate L3. Finally, it was dried in a dryer at 120°C for 1 minute, and then dried at 60°C and 10 N / cm 2 The laminate was then left at room temperature for 48 hours to obtain a laminate sheet.
[0081] [Example 2-3] Except for changing the composition and application amount of the resin composition for the magnetic layer and changing the magnetic material, thickness, and basis weight of the magnetic layers C1 to C3 to those shown in Table 2, a laminate sheet was prepared in the same manner as in Example 2-1, in which the layers were laminated in the following order: double-sided vapor deposition film A1, magnetic layer C1, binder layer B1, nonwoven fabric layer N1, binder layer B2, double-sided vapor deposition film A2, magnetic layer C3, binder layer B3, nonwoven fabric layer N2, binder layer B4, and double-sided vapor deposition film A3.
[0082] [Example 2-4] Except for changing the composition and application amount of the resin composition for the magnetic layer and changing the magnetic material, thickness, and basis weight of the magnetic layers C1 to C3 to those shown in Table 2, a laminate sheet was prepared in the same manner as in Example 2-2, in which the layers were laminated in the following order: single-sided vapor deposition film A1, magnetic layer C1, binder layer B1, nonwoven fabric layer N1, binder layer B2, single-sided vapor deposition film A2, magnetic layer C3, binder layer B3, nonwoven fabric layer N2, binder layer B4, and single-sided vapor deposition film A3.
[0083] [Comparative Example 2-1] The laminate L1 was not produced. Instead of the laminate L3, the above-mentioned resin composition for the binder layer was applied to the surface of the magnetic layer C3 side of the laminate L2 using a comma coater so as to be 30 g (dry weight) per square meter. A polyester nonwoven fabric was then laminated on the applied resin composition for the binder layer. After that, the polyester nonwoven fabric was dried in a dryer at 120°C for 1 minute, and then dried at 60°C and 10 N / cm. 2 A laminate was prepared in the same manner as in Example 2-1, except that the laminate L3' was prepared by thermocompression bonding under a pressure condition of 1000 V and then left at room temperature for 48 hours, and a laminate L3' was prepared in which the double-sided vapor-deposition film A2, the magnetic body layer C3, the binder layer B3, and the nonwoven fabric layer N2 were laminated in this order. A laminate sheet was obtained in which the double-sided vapor-deposition film A1, the magnetic body layer C1, the binder layer B1, the nonwoven fabric layer N1, the binder layer B2, the double-sided vapor-deposition film A2, the magnetic body layer C3, the binder layer B3, and the nonwoven fabric layer N2 were laminated in this order.
[0084] [Comparative Example 2-2] A method for manufacturing a laminate sheet in which a magnetic layer C0, a double-sided vapor-deposited film (conductive layer) A1, a binder layer B1, a nonwoven fabric layer N1, a binder layer B2, a magnetic layer C2, a double-sided vapor-deposited film (conductive layer) A2, a binder layer B3, a nonwoven fabric layer N2, a binder layer B4, and a double-sided vapor-deposited film (conductive layer) A3 are laminated in this order is described below. The above resin composition for binder layer was applied to the surface of the double-sided deposition film A3 with a comma coater so as to be 30 g (dry weight) per square meter, and a polyester nonwoven fabric was laminated on the resin composition for binder layer. Thereafter, the polyester nonwoven fabric was dried in a dryer at 120°C for 1 minute, and then dried at 60°C and 10 N / cm 2 The laminate was then allowed to stand at room temperature for 48 hours to obtain a laminate L1 in which the nonwoven fabric layer N2, the binder layer B4, and the double-sided vapor deposition film A3 were laminated in this order. The above-mentioned resin composition for magnetic layer was applied to the surface of the double-sided deposition film A2 by a comma coater so as to be 150 g (dry weight) per square meter, and then dried at 150°C for 3 minutes using a dryer to form a magnetic layer C2 on the surface of the double-sided deposition film A2, thereby obtaining a laminate L2'. The magnetic layer C2 had a basis weight of 150 g / m 2 The weight of the magnetic material, Sendust, is 100 g / m 2 It was. The above resin composition for binder layer was applied to the surface of the double-sided deposition film A2 side of the laminate L2' with a comma coater so as to be 30 g (dry weight) per square meter, and the surface of the nonwoven fabric layer N2 side of the laminate L1 was laminated onto the applied resin composition for binder layer. Thereafter, the laminate was dried in a dryer at 120°C for 1 minute, and then dried at 60°C and 10 N / cm 2 and then left at room temperature for 48 hours to obtain a laminate L3' having a magnetic layer C2, a double-sided vapor-deposited film A2, a binder layer B3, a nonwoven fabric layer N2, a binder layer B4, and a double-sided vapor-deposited film A3 laminated in this order. The above-mentioned resin composition for the magnetic layer was applied to the surface of the double-sided deposition film A1 by a comma coater at 150 g (dry weight) per square meter, and then dried for 3 minutes at 150° C. using a dryer to form a magnetic layer C0 on the surface of the double-sided deposition film A1. Next, the above-mentioned resin composition for the binder layer was applied to the surface of the double-sided deposition film A1 by a comma coater at 30 g (dry weight) per square meter, and a polyester nonwoven fabric was attached to the surface of the applied resin composition for the binder layer, and then dried for 1 minute in a dryer at 120° C. and then dried at 60° C. and 10 N / cm. 2 The laminate was then heated and pressed under a pressure of 150 g / m2 and left at room temperature for 48 hours to obtain a laminate L4' in which the magnetic layer C0, the double-sided deposition film A1, the binder layer B1, and the nonwoven fabric layer N1 were laminated in this order. 2 The weight of the magnetic material, Sendust, is 100 g / m 2 It was. The above-mentioned resin composition for binder layer was applied to the surface of the magnetic layer C2 side of the laminate L3' by a comma coater so as to be 30 g (dry weight) per square meter, and then the surface of the nonwoven fabric layer N1 side of the laminate L4' was laminated on the resin composition for binder layer applied to the laminate L3'. Finally, it was dried for 1 minute in a dryer at 120°C, and then dried at 60°C and 10 N / cm 2 The laminate was then left at room temperature for 48 hours to obtain a laminate sheet.
[0085] [Comparative Example 2-3] A laminate sheet was produced in the same manner as in Comparative Example 2-2, except that the following laminate L1' was prepared and used instead of the laminate L1.
[0086] <Preparation of Laminate L1'> The above-mentioned resin composition for the magnetic layer was applied to the surface of the polyester nonwoven fabric using a comma coater at 150 g (dry weight) per square meter, and then dried using a dryer at 150°C for 3 minutes to form a magnetic layer C4 on the surface of the nonwoven fabric layer N2, thereby obtaining a laminate L1' in which the nonwoven fabric layer N2 and the magnetic layer C4 are laminated in that order.
[0087] [Comparative Example 2-4] A laminate sheet was produced in the same manner as in Comparative Example 2-2, except that aluminum foil was used instead of the double-sided vapor deposition film.
[0088] [Comparative Example 2-5] A laminate sheet was prepared in the same manner as in Example 2-1, except that aluminum foil was used instead of the double-sided vapor deposition film, and the composition and application amount of the resin composition for the magnetic layer were changed, and the magnetic material, thickness, and basis weight of the magnetic layers C1 to C3 were changed to those shown in Table 2.
[0089] [Comparative Example 2-6] The resin composition for binder layer was applied to one surface of the aluminum foil A1 using a comma coater so as to be 30 g (dry weight) per square meter, and the surface of the applied resin composition for binder layer was coated with a thickness of 385 μm and a basis weight of 60 g / m. 2 A polyester nonwoven fabric (model number: 6551N) manufactured by Toyobo Co., Ltd. was attached to the sheet, and then it was dried for 1 minute in a dryer at 120°C, and then dried at 60°C, 10N / cm 2 The laminate was then heat-pressed under a pressure of 10 N / cm and left at room temperature for 48 hours to obtain a laminate in which the aluminum foil A1, the binder layer B1, and the nonwoven fabric layer N1 were laminated in this order. The resin composition for the binder layer was then applied to the surface of the laminate opposite to the aluminum foil A1 using a comma coater at a rate of 30 g (dry weight) per square meter, and the polyester nonwoven fabric or aluminum foil was attached to the surface of the applied resin composition for the binder layer. The laminate was then dried in a dryer at 120°C for 1 minute, and then dried at 60°C and 10 N / cm. 2 By repeatedly subjecting the laminate to thermocompression bonding under the pressure condition of 100° C. and leaving it at room temperature for 48 hours, a laminate was obtained in which aluminum foil A1, binder layer B1, nonwoven fabric layer N1, binder layer B2, aluminum foil A2, binder layer B3, nonwoven fabric layer N2, binder layer B4, and aluminum foil A3 were laminated in this order.
[0090] The layer configurations and physical properties of each layer of the laminate sheets in the examples and comparative examples, as well as the shielding properties of the laminate sheets, are shown in Table 2. In the column for the basis weight of the magnetic layer, the values in parentheses are the basis weight of only the magnetic material, excluding the resin.
[0091] [Table 2]
[0092] In Examples 1-1 to 1-4 and 2-1 to 2-4, the laminated sheets have a predetermined layer structure, and therefore are excellent in electromagnetic wave shielding properties.
Claims
1. An electromagnetic wave shielding sheet comprising a first conductive layer, a second conductive layer, and a third conductive layer, one main surface of the electromagnetic wave shielding sheet is the first conductive layer, the other main surface is the second conductive layer, and the third conductive layer is between the first conductive layer and the second conductive layer, a first magnetic layer between the first conductive layer and the third conductive layer, and a second magnetic layer between the third conductive layer and the second conductive layer; The electromagnetic wave shielding sheet is characterized in that the first conductive layer, the second conductive layer, and the third conductive layer all have a laminated structure in which a conductive film having a thickness of 25 to 150 nm is formed on at least one surface of a resin layer, and the first magnetic layer and the second magnetic layer all contain a magnetic material.
2. 2. The electromagnetic shielding sheet according to claim 1, wherein the conductive material constituting the conductive film includes at least one material selected from the group consisting of conductive polymers, metals, metal oxides, and carbon-based materials.
3. 2. The electromagnetic shielding sheet according to claim 1, wherein the magnetic material is a soft magnetic material.
4. 2. The electromagnetic wave shielding sheet according to claim 1, wherein the total thickness of the conductive films included in the electromagnetic wave shielding sheet is 3 [mu]m or less.
5. 2. The electromagnetic shielding sheet according to claim 1, further comprising a nonwoven fabric layer as an intermediate layer.
6. The electromagnetic wave shielding sheet according to claim 5 , wherein the nonwoven fabric layer contains a polyester resin.
7. 7. The electromagnetic shielding sheet according to claim 1, having a thickness of 900 μm or less, a magnetic field shielding property at 100 MHz measured by the KEC method of 20 dB or more, and an electric field shielding property at 10 MHz of 70 dB or more.
Citation Information
Patent Citations
Inflammable electromagnetic wave shield laminate and inflammable electromagnetic wave shielding wall material produced using the same
JP2019179786A
Multilayer electromagnetic shielding composite
JP2022075645A